Clonazepam associated hypothyroidism: Aforethought on a concealed dilemma - Rupam Gill,Dipanjan Bhattacharjee,Navin A. Patil,Shripathy M. Bhat (Journal of Applied Pharmaceutical Science, 2016)
Subclinical hypothyroidism or mild thyroid failure is a familiar problem, with a prevalence of 3-15% in a population without any known overt thyroid disorder. The prevalence increases with age and is relatively higher among females. Subclinical hypothyroidism is defined as serum thyroid stimulating hormone (TSH) levels above the upper limit of normal (4 mU/L) while the triiodothyronine (T3) and thyroxine (T4) enduring within the normal range. Additionally, there exists a log-linear relationship between TSH and circulating T3 and T4; hence, measurement of serum TSH becomes mandatory for diagnosing mild thyroid failure when free T3and T4 are lying within normal limits. Though, autoimmune thyroid disease is the most common cause for elevated TSH; thyroid functions can be afflicted by long-term consumption of drugs like lithium, amiodarone. The causal relationship between benzodiazepine class of drugs, particularly clonazepam and subclinical hypothyroidism has never been established clinically, yet there are some pre-clinical studies to claim the effect of benzodiazepine on thyroid functions; operating at various levels – hypothalamus, thyroid gland, peripheral cells and nuclear receptors. Henceforth, we would like to report a rare occurrence of subclinical hypothyroidism in an elderly female receiving clonazepam for her underlying psychiatric illness.
Keywords: Benzodiazepine,Thyroid stimulating hormone (TSH),Naranjo’s algorithm,Triiodothyronine (T3),Clonazepam.